"Jurisprudential and legislative responses to 'disguised employment' - an analysis of the employee/independent contractor dilemma" - Davies, Kristofer (Centre for Law and Society, 2026)
The introduction of the new Labour Relations Act (LRA)1 stood set to revolutionize South African employment law. With its noble aims of 'advancing economic development, social justice, labour peace and the democratization of the workplace'2, it was hailed by some as a legislative masterpiece. However, is this really the case? It is open to debate whether the Act goes far enough in its attempt to give effect to the constitutional right to fair labour practices.